CLARIFYING LEARNERS' CAREER ORIENTATIONS IN THE CONTEXT OF DIGITAL TRANSFORMATION: CHALLENGES AND SOLUTIONS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The digital transformation revolutionizes career orientations, demanding adaptable education systems to align with new competencies. This article examines challenges faced by learners, such as skill gaps, and provides solutions like enhanced career guidance and integrated digital curricula. Recommendations are grounded in theoretical frameworks and empirical evidence, promoting a responsive and inclusive approach to digital-era career preparation.